Primary incidence of the thyroid system and iodine supply of the adult population in the Zavodskoy district of Minsk - Puhteeva, Irina; Petrenko, Sergei; Sidorovich, Anna (Journal of the Belarusian State University. Ecology, 2023)
Currently, iodine deficiency diseases are one of the most common diseases of non-infectious origin. In the Republic of Belarus, preventive measures are being taken to eliminate the problem of iodine deficiency, in particular, a state strategy has been developed and implemented, the main measure of which is the mandatory use of only iodized salt in the food industry and public catering. Despite the measures taken, the problem of iodine deficiency remains relevant, especially for children and pregnant women. According to the results of the assessment of iodine sufficiency in the world, published by the RIAC on Surveillance for Iodine Deficiency Diseases (ICCIDD) – a global non-commercial, spheral need created for the use of iodine deficiency and the consequences of its negative examination on health, adequate iodine intake is provided in the Republic of Belarus. In 2016, the Global Iodine Network published maps characterizing iodine sufficiency for two main assessment categories – school-age children and pregnant women, confirming the status of the Republic of Belarus as a country with adequate iodine sufficiency. However, despite the results achieved, from the standpoint of medical monitoring, the quality of studies conducted to monitor the iodine supply of the population, the risks of excessive salt intake remain relevant. In this paper, a comparative analysis of the dynamics of the primary incidence of thyroid pathology in the population of the Zavodskoy district of the city of Minsk for the period 2016–2020 was carried out. According to the results of the analysis, a positive trend in the primary incidence of simple goiter, nodular non-toxic goiter and thyroiditis was revealed, while the dynamics of the primary incidence of hypothyroidism did not change. According to the data presented, the presence of iodine deficiency with a median urinary iodine excretion of 196.15 μg/l was revealed in pregnant women of the Zavodskoy district of Minsk in 2021. An analysis of the questionnaire survey of the nature of the nutrition of pregnant women showed that most of the surveyed do not know about the benefits of using iodized salt for the development of the fetus, and therefore the reason for the formation of iodine deficiency in the body of pregnant women is the insufficient intake of iodine in the body and refusal to take iodine preparations. In the surveyed region, 22 % of women do not comply with the prescription of endocrinologists about the need to take iodine-containing drugs.
Keywords: профилактика йододефицита; pregnant women; iodized salt; iodine deficiency; dynamics of primary morbidity; prevention of iodine deficiency